The association Between Development and Progression of Multinodular Goiter and Thyroid-Stimulating hormone Receptor Gene D727E and P52T Polymorphisms - Bayram, B.; Sonmez R.; Bozari S.; Onlu H.; Turkoglu Z.; Mutlu F.S. (My University, 2013)
Aim: This study has been performed on a Turkish population with multinodular goiter (MNG) to investigate the thyroid-stimulating hormone receptor (TSHR) gene D727E and P52T polymorphisms. Methods: DNA samples were isolated from 300 patients with MNG and 142 controls. Polymerase chain reaction-restriction fragment length polymorphism and agarose gel electrophoresis were used. Results: The D727E polymorphism G-allele frequency and the CG and GG genotypes were significantly higher in patients with MNG. However, there was no significant difference in the P52T polymorphism between patients and control subjects. Conclusions: As a conclusion, the D727E polymorphism G allele may be related to MNG development in the studied population. © 2013, Mary Ann Liebert, Inc.
PubMed ID: 23336574